Sprouted sorghum grain for finishing swine - Allee, G.L.; Koch, B.A.; Knake, R.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In a three-week feeding trial for 30 growing pigs (70 lbs.), we compared diets formulated by using 1973 sprout damaged sorghum grain from two Kansas areas. No palatability problems were noted, weight gains were similar to those of pigs fed undamaged 1972 sorghum. Feed consumption of diets based on sprout damaged sorghum grain was higher, consequently, resulted in poorer feed conversion. Though the data may indicate slightly higher feed requirements, they should be considered only as preliminary, because results were based on only a short feeding period and few animals.
Swine Industry Day 1974 is known as Swine Day, 1974
Keywords: Swine; Sorghum; Finishing pigs